Sistem Pengemasan Makaroni Berdasarkan Berat pada Konveyor Berbasis Mikrokontroler - Eva Damayanti; Sandithya Rizky Mandiri (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2019)
Abstract - Productivity is very important, because the level of productivity will be directly proportional to the profits obtained. To protect the product from the dangers of pollution and physical disturbances such as friction, impact, and vibration. Then the product needs packaging to minimize potential damage and protect the products inside. In addition packaging is one of the important parts in production, because packaging is the final stage of a production. Packaging provides forms that make it easier for products to be stored, transported and distributed. Packaging is also a coordinated system to prepare goods to be ready for sale and use. If the producers do packaging, by using a lot of people as workers, it will have an impact on the amount of production costs, and unstable productivity levels. This research aims to reduce production costs and production time more efficiently. This study uses the latest technology in the field of packaging, which uses Mega Arduino as a system controller, and uses conveyors as a driver of macaroni, where later the macaroni will be processed in stages. In conveyors using dc motors as conveyor drives, servo motors as opening and closing macaroni storage. In addition, load cells (heavy sensors) are useful for comparing the amount of weight with electricity.Where the load cell will be used as the weight limit between macaroni and the weight value we want. Keywords: productivity, packaging, arduino mega, load cell, motor servo, conveyor.